Methodological lessons from a cohort study of high risk women in Tanzania. (30th November 2004) - Hoffmann, O; Zaba, B; Wolff, B; Sanga, E; Maboko, L; Mmbando, D; von Sonnenburg, F; Hoelscher, M
Abstract : Objectives: To describe the development, characteristics, and follow up of a high risk cohort of women in Tanzania. Differences in social background and sexual behaviour of women working in traditional and modern alcohol selling workplaces are shown. Methods: Data from questionnaires four months before the enrolment of the cohort, at enrolment, and at 32 months were compared. Key informant interviews, social mapping exercises, and focus group discussions were held before the start of the cohort. Results: In the absence of organised prostitution, two different groups of women with high risk exposure were identified during the baseline survey: female workers in modern alcohol selling places such as bars, guesthouses, and restaurants (barmaids) and in traditional places (local brew sellers). Overall, the population had a mean age of 27.7 years with barmaids tending to be younger (24.3 years) than local brew sellers (34.2 years). The main duration of stay in the current workplace was 2.1 years (barmaids 0.9 years; local brew sellers 4.1 years). Barmaids were more likely to have paying casual sex partners than local brew sellers and used condoms more regularly. Local brew sellers tend to be more stable with only 10% lost to follow up after 32 months compared with 24.4% of the bar workers. Conclusions: Preliminary work revealed major differences in characteristics and behaviour between women working in modern and traditional alcohol selling outlets. Thorough preparation of the study, close monitoring of the cohort, and provision of selected benefits resulted in high retention rates over a 32 month project in a highly mobile population.